2018
DOI: 10.1111/ane.12955
|View full text |Cite
|
Sign up to set email alerts
|

Increase of frontal neuronal activity in chronic neglect after training in virtual reality

Abstract: The current pilot study demonstrates that a novel multisensory VR intervention has the potential to benefit patients with chronic neglect in respect of behaviour and brain changes. Specifically, the fMRI results show that strategic processes (top-down control during attentional cuing) were enhanced by the intervention. The findings increase knowledge of the plasticity processes underlying positive rehabilitation effects from RehAtt in chronic neglect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 33 publications
2
40
1
1
Order By: Relevance
“…Previous studies also showed that VR could improve movement and body position perception [28]. In chronic neuropathic pain, a VR-based treatment could induce analgesia in association with an improved embodiment sensation [60].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also showed that VR could improve movement and body position perception [28]. In chronic neuropathic pain, a VR-based treatment could induce analgesia in association with an improved embodiment sensation [60].…”
Section: Discussionmentioning
confidence: 99%
“…142 Interestingly, 2 years later, authors used fMRI to evaluate changes in brain activity during Posner′s Cueing Task after RehAtt™ rehabilitation. The amelioration of neglect symptoms was associated with increased brain activity in the pre-frontal and temporal cortex during attentional cueing, 143 suggesting enhancement of topdown strategies, and increased inter-hemispheric restingstate functional connectivity of the dorsal attentional network. 144 A final promising protocol was tested in a single-blind dose-response study in healthy subjects, by using VR as an alternative to real prisms.…”
Section: Virtual Realitymentioning
confidence: 92%
“…Neuroplasticity: the App permits to use scenarios specifically designed following principles that regulate and facilitate neuroplasticity (the neurobiological process basis of recovery of cognitive and motor functions), such as exercise intensity, exercise frequency, “enriched stimulation” ( Cheung et al, 2014 ; Ekman et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%